Aptamer-iRNAs as Therapeutics for Cancer Treatment - Mario M. Soldevilla; Daniel Meraviglia-Crivelli de Caso; Ashwathi P. Menon; Fernando Pastor (Pharmaceuticals, 2018)
Aptamers are single-stranded oligonucleotides (ssDNA or ssRNA) that bind and recognize their targets with high affinity and specificity due to their complex tertiary structure. Aptamers are selected by a method called SELEX (Systematic Evolution of Ligands by EXponential enrichment). This method has allowed the selection of aptamers to different types of molecules. Since then, many aptamers have been described for the potential treatment of several diseases including cancer. It has been described over the last few years that aptamers represent a very useful tool as therapeutics, especially for cancer therapy. Aptamers, thanks to their intrinsic oligonucleotide nature, present inherent advantages over other molecules, such as cell-based products. Owing to their higher tissue penetrability, safer profile, and targeting capacity, aptamers are likely to become a novel platform for the delivery of many different types of therapeutic cargos. Here we focus the review on interfering RNAs (iRNAs) as aptamer-based targeting delivered agents. We have gathered the most reliable information on aptamers as targeting and carrier agents for the specific delivery of siRNAs, shRNA, microRNAs, and antisense oligonucleotides (ASOs) published in the last few years in the context of cancer therapy.